The Saga of Desi Fizz: Bindu Jeera - Rizwana, M.; Singh, Padmalini (AMC Indian Journal of Entrepreneurship, 2020)
India is a diverse country with 29 states, each having their own regional beverages. Inspite of the popularity of conventional homemade drinks, packaged beverages are overruling the Indian consumers due to the strenuous process of preparing homemade drinks. Indian consumers are constantly looking for more convenience by procuring substitutes, that is, RTD (Ready-To-Drink) soft drinks. The soft drink market that is flooded with similar aerated substitutes has created an opportunity for unconventional drinks to find their space by satisfying the Indian palate. A common man, Mr. Sathya Shankar with uncommon ideas was the first to seize this opportunity by venturing into the business of unique blending of Indian flavour of Cumin (‘Jeera’) into western Cola and he created ‘Bindu Jeera'drink. The objective of this case was to highlight how an indigenous product 'Bindu Jeera' despite receiving negative feedback and reviews from its stake holders could create its market share within a short span of time. The case discusses the vibrant marketing strategies adopted by the first mover Shankar Groups on its journey to change the landscape of Indian soft drink industry. It also attempts to evaluate the important factors a company should consider for developing a product with certain unique characteristics that is ascertained to outperform its competition. Further studies show how Shankar group could reach the nook and corner of the market with its strong distribution network inspite of having constraints in advertising budget. The case also attempted to find out to what extent the strategies of Shankar group could counteract the retaliation from established global brands. The case is mainly focussed on students studying M.B.A. and other business management courses such as Entrepreneurship Development, Sales and Distribution Management, Brand Management, Supply Chain Management, and other Marketing Management curriculum.